Evaluasi dan Perbaikan Proses Bisnis Menggunakan Business Process Improvement (BPI) (Studi Kasus: Dinas Pengendalian Penduduk, Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Kediri) - Higam Saiful Sadzali; Nanang Yudi Setiawan; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
DP2KBP3A Kab. Kediri is a government institution that has functions of population controls,a planned family, empowerment of women and the protection of the childrens. In running the business process, there are some potential problems that can affectto achieve the vision and mission. Data entry error, poor document archiving, lack of accuracy in performing tasks, hardware errors and non-value activities, they are some of the problems that found in the current business process. Therefore it is necessary for analyze and evaluate to improve business process to run optimally. This research uses Value Shop Analysis to identify main business process and support business process, then Failure Mode and Effect Analysis (FMEA) to analyze the root cause of the problen then used as an evalutaion of business prosesses and Business Process Improvement (BPI) method to get business process recommendations. Based on the result of simulation of current business process and recommendation, it is found that the time analysis of business process prosperous family data and analysis has increased the effectiveness of time up to 73,36%. So it can be concluded the business process recommendations can improve performance better.